HUBUNGAN SELF EFFICACY DENGAN EMOTION FOCUSED COPING SAAT PEMBELAJARAN JARAK JAUH PADA MAHASISWA RANTAU UNIVERSITAS TEKNOLOGI SUMBAWA DI MASA NEW NORMAL COVID-19 - Imammul Insan; Fina Nurul ‘Izzah (JURNAL PSIMAWA, 2021)
This study aims to determine the relationship between Self Efficacy variable with Emotion Focused Coping during long-distance learning on overseas students at Sumbawa University of Technology during the COVID-19 New Normal Adaptation. This study uses a quantitative correlation technique. The sampling technique uses cluster sampling and the determination of the number of samples is assisted by using the Slovin formula, the critical value or the accuracy limit is of 10%. The research sample is 85 students of Sumbawa University of Technology. The research data are obtained by using research instruments in the form of two scales, namely the Self Efficacy scale and Emotion Focused Coping. Based on the results of the data analysis that has been conducted, there is a relation between self-efficacy and Emotion Focused Coping. This can be seen from the significance value of 0.000 <0.05 with a correlation value of0.508. Both of these variables have a positive correlation, or a unidirectional relation, which means an increase in Self Efficacy followed by an increase in Emotion Focused Coping, and vice versa, a decrease in Self Efficacy is followed by a decrease in Emotion Focused Coping. The correlation coefficient value of 0.508 is included in the moderate correlation strength category with the Self Efficacy variable with Emotion Focused Coping during long-distance learning on overseas students at Sumbawa University of Technology during the COVID-19 New Normal Adaptation.